Frailty Is Predictive of Adverse Postoperative Events in Patients Undergoing Lumbar Fusion. (September 2017) - Leven, Dante M.; Lee, Nathan J.; Kim, Jun S.; Kothari, Parth; Steinberger, Jeremy; Guzman, Javier; Skovrlj, Branko; Shin, John I.; Phan, Kevin; Caridi, John M.; Cho, Samuel K.
Study Design: Retrospective study of prospectively collected data. Objective: To analyze the modified frailty index (mFI) as a predictor of adverse postoperative events following posterior lumbar fusion. Methods: The American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) database including all adult patients undergoing posterior lumbar interbody fusion or transforaminal lumbar interbody fusion between 2005 and 2012. Outcomes measured included mortality, postoperative complications, length of stay, reoperations, and readmissions. The previously described mFI was calculated, and univariate and multivariate logistic regression analysis were used to analyze risk factors associated with morbidity, mortality, and adverse postoperative events. This study was qualified as exempt by the Mount Sinai Hospital Institutional Review Board. Results: A total of 6094 patients met inclusion criteria. The mean mFI was 0.087(0-0.545). Increasing mFI score was associated with increased complications, reoperations, prolonged length of stay (LOS), and morbidity ( P < .05). As the mFI score increased from 0.27 (3/11 variables present) to ≥0.36 (4/11), the rate of any complication increased from 26.8% to 35% ( P < .0001), sepsis 2.4% to 5.2% ( P < .0001), wound complications 4.4% to 6.5% ( P < .0001), unplanned readmissions 4.7% to 20% ( P = .02), and urinary tract infection 4.1% to 10.4% ( P < .0001). An mFI of ≥0.36 was an independent predictor of any complication (odds ratio [OR]= 2.2, 95% confidence interval [CI] = 1.3-3.7), sepsis (OR = 6.3, 95%, CI = 1.8-21), wound complications (OR = 2.9, 95% CI = 1.1-8.2), prolonged LOS (OR = 2.3, 95% CI = 1.4-3.7), and readmission (OR = 4.3, 95% CI = 1.5-12.7). Conclusion: Patients with higher mFI scores (≥ 4/11 variables) are at a significantly higher risk of major complications, readmissions, and prolonged LOS following lumbar fusion.